Gloomy prospects: The Konstanz Inequality Barometer shows that inequality is perceived to have increased - Marius R. Busemeyer; Nanna Lauritz Schönhage; Sharon Baute; Luna Bellani; Guido Schwerdt (University of Konstanz, Cluster of Excellence "The Politics of Inequality", Das Progressive Zentrum e.V., 2023)
Data from the new wave of the Konstanz Inequality Barometer shows that people in Germany perceive a widespread increase of inequality in income and wealth and barely distinguish between income and wealth inequality. This is despite the fact that wealth inequality is significantly larger than income inequality. At the same time, the actual level of inequality is still underestimated in some respects. Concerning the prospects of the younger generation, many people, especially supporters of the right-wing populist AfD, are rather negative. Less pessimism is found among supporters of the center-right parties, CDU/CSU and FDP.
urn:nbn:de:bsz:352-2-19m98smt0dovk9
Keywords: 320